Exchange Pass-through into Price level in Libya During the period (Q12010-Q42021) - صالح على عيسى; المانع أحمد (Dirasat in Economics and Business, 2024)
This study examines the exchange rate pass-through into the consumer price index, as a measure of the domestic price level in Libya, using quarterly data covering the period from Q12010 to Q42021. To test the exchange rate pass-through, the non-linear autoregressive distributed model (NARDL) was applied, where two main indicators of the exchange rate were employed as explanatory variables in two separate models, namely the parallel exchange rate and the parallel real exchange rate, in addition to including other monetary and fiscal variables, that are the money supply, and international oil prices. The study concluded that there is an incomplete and high transmission of the effect of changes in the parallel real exchange rate to the consumer price index in the long run. The results also demonstrated the asymmetric response of the consumer price index to positive and negative shocks to the exchange rate. The results also showed an incomplete and modest transmission of changes in the parallel nominal exchange rate into the consumer price index. It is obvious from the results that the parallel real exchange rate model is the closest in explaining the phenomenon of exchange rate pass-through to the general price level in Libyan economy.